Analisis Penerimaan Petani Penyadap Getah Pinus Di Hutan Kemasyarakatan Sipatuo Lembang Pa’tengko Kecamatan Mengkendek Kabupaten Tana Toraja - Kada’, Irfan Mesa; Walangitan, Hengki D.; Kalitouw, Devitha W. (Sam Ratulangi University, 2023)
This study aims to analyze how much pine resin tapping farmers receive and describe the marketing channels of pine resin tapping farmers in the Sipatuo Community Forest, Lembang Pa'tengko, Mengkendek District, Tana Toraja Regency. The variables to be observed in this study are pine resin production, tapper farmers' revenue, socio-economic factors, management of Sipatuo HKm, and marketing channels. The data collection method was carried out through surveys and distributing questionnaires to pine resin tappers as many as 40 respondents. Data is analyzed descriptively and revenue is calculated based on the Total Revenue equation. The results showed that the Sipatuo HKm was a limited production forest managed by the Lembang Pa'tengko community, the tree stands that were managed were a government reforestation program in 1976-1978. Furthermore, the results of the analysis of the average tapper acceptance of Rp6,300,450 thus the reception of tappers at HKm Sipatuo is sufficient to meet household needs because the average acceptance of tappers exceeds the UMP of South Sulawesi. Marketing of pine resin in HKm is carried out on average once a month, with a selling price of pine resin, which is Rp. 9,500.00 where the pine resin is sold to partners as one intermediary, then the pine resin is sent to CV.Pindo Indonesia in Makassar as a large collector.